Dual Effect of Methylprednsolone Pulses on Apoptosis of Peripheral Leukocytes in Patients with Renal Diseases - Stratta, P.; Canavese, C.; Fenoglio, R.; Priolo, G.; Grillo, A.; Aimo, G.; Quaglia, M.; Pagni, R. (International journal of immunopathology and pharmacology, 2006)
It is well known that change in apoptosis may modulate the natural story of illness, and that many drugs may act through modulation of apoptosis, but the role of steroids in acting through apoptosis in different settings, including renal diseases, has still to be elucidated. We studied the in vivo effects of steroids by oral assumption (10 to 25 mg/deltacortene) or by intravenous pulses (300 to 1000 mg/dose) on apoptosis and cellular subsets of peripheral lymphocytes, by evaluating DNA-fragmentation and lymphocyte subsets in 79 subjects: 22 controls and 57 patients with various renal diseases (25 Lupus-GN, 19 membranous-GN (MGN), 6 rapidly progressive-GN (RPGN), 2 acute interstitial nephritis (AIN), 5 on chronic dialysis. Baseline apoptosis was present in 1/22 (4.5%) of controls, 3/25 (12%) SLE, 2/6 (33.3%) RPGN and 10/19 (52.6%) MGN. A significant decrease in CD3+CD8+ cell count and a significant increase of the CD3+CD4/CD3+CD8+ ratio were found in apoptosis-positive subjects. DNA fragmentation did not change after oral steroids, paralleling a 22 to 32% decrease in total lymphocytes. Following intravenous methylprednisolone pulses, a deeper drop of all lymphocyte subsets was observed, while DNA fragmentation turned from present to absent in 2 MGN, but not in 2 RPGN, and from absent to present in 1 ARF and 1 SLE, independently of the dosage. We demonstrated that the presence of apoptosis in renal diseases is associated with decreased CD3+CD8+ cell count. Furthermore, steroid intravenous pulses, besides inducing a profound decrease in lymphocyte subsets, do exert a dual effect on baseline leukocyte apoptosis, eventually leading to a reversal of baseline patterns, either turning from negative to positive or from positive to negative. Oral steroid therapy did not influence baseline apoptosis.